2006
DOI: 10.2174/092986706778521968
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Coumarins and 1-Azacoumarins as Versatile Biodynamic Agents

Abstract: Coumarins, also referred as benzopyran-2-ones, and their corresponding nitrogen counterpart, 1-azacoumarins also referred to as carbostyrils, are a family of nature-occurring lactones and lactams respectively. The plant extracts containing coumarin-related heterocycles, which were employed as herbal remedies in early days, have now been extensively studied for their biological activities. These investigations have revealed their potentials as versatile biodynamic agents. For example, coumarins with phenolic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(68 citation statements)
references
References 113 publications
1
67
0
Order By: Relevance
“…Coumarin and its derivatives are considered as phenylpropanoids (Kulkarni et al, 2006). Coumarins are reported to exhibit anticonvulsant (Luszczki et al, 2010), antihyperglycemic (Ramesh & Pugalendi, 2006), antimyotoxic (Toyama et al, 2011, antiinflammatory and antiviral activities (Selim & Ouf, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin and its derivatives are considered as phenylpropanoids (Kulkarni et al, 2006). Coumarins are reported to exhibit anticonvulsant (Luszczki et al, 2010), antihyperglycemic (Ramesh & Pugalendi, 2006), antimyotoxic (Toyama et al, 2011, antiinflammatory and antiviral activities (Selim & Ouf, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…5). Substantially cytotoxic values have been reported by some coumarin derivatives containing halogen groups (Kulkarni et al, 2006). Thus, it can be concluded that the key role in the anti-breast cancer activity of this compound class is performed by the presence of p-chloro substituents.…”
Section: Evaluation Of Cytotoxicity Activity Against Breast Cancer Cementioning
confidence: 97%
“…Benzopyrones are an important class of oxygenated heterocycles, widely distributed in plants, including edible vegetables and fruits [79] and many of them have broad and interesting ranges of biological activities [80][81][82][83]. The two more important benzopyrone derivatives are the chromones and coumarins.…”
Section: Benzopyrones: Coumarins and Chromonesmentioning
confidence: 99%